Nintedanib, a triple angiokinase inhibitor, enhances cytotoxic therapy response in pancreatic cancer. Issue 1 (1st March 2015) - Awasthi, Niranjan; Hinz, Stefan; Brekken, Rolf A.; Schwarz, Margaret A.; Schwarz, Roderich E.
Highlights: Nintedanib, a triple angiokinase inhibitor, was evaluated in pancreatic cancer. It inhibited in vitro proliferation of PDAC cells and blocked PI3K/MAPK activity. Nintedanib inhibited local tumor growth and enhanced gemcitabine response. Nintedanib therapy increased animal survival and enhanced gemcitabine response. Nintedanib-controlled mechanisms are potential targets for improved PDAC therapy. Abstract: Angiogenesis remains a sensible target for pancreatic ductal adenocarcinoma (PDAC) therapy. VEGF, PDGF, FGF and their receptors are expressed at high levels and correlate with poor prognosis in human PDAC. Nintedanib is a triple angiokinase inhibitor that targets VEGFR1/2/3, FGFR1/2/3 and PDGFRα/β signaling. We investigated the antitumor activity of nintedanib alone or in combination with the cytotoxic agent gemcitabine in experimental PDAC. Nintedanib inhibited proliferation of cells from multiple lineages found in PDAC, with gemcitabine enhancing inhibitory effects. Nintedanib blocked PI3K/MAPK activity and induced apoptosis in vitro and in vivo . In a heterotopic model, net local tumor growth compared to controls (100%) was 60.8 ± 10.5% in the gemcitabine group, −2.1 ± 9.9% after nintedanib therapy and −12.4 ± 16% after gemcitabine plus nintedanib therapy. Effects of therapy on intratumoral proliferation, microvessel density and apoptosis corresponded with tumor growth inhibition data. In a PDAC survival model, median animal survival after gemcitabine, nintedanib and gemcitabine plus nintedanib was 25, 31 and 38 days, respectively, compared to 16 days in controls. The strong antitumor activity of nintedanib in experimental PDAC supports the potential of nintedanib-controlled mechanisms as targets for improved clinical PDAC therapy.